ШЫҒЫС ҲӘМ ТҮРКИЙ ӘДЕБИЯТЫНДАҒЫ ЖАНРЛЫҚ ДИФФУЗИЯ ДӘСТҮРЛЕРИ - Матимов, Кошкарбай Генжебаевич (FAN va JAMIYAT, 2026)
The article examines the historical and theoretical foundations of genre diffusion in Eastern and Turkic literature, its role and characteristics in the process of artistic development. Genre diffusion is analyzed as a mechanism for the intermingling of artistic genres and the emergence of new intermediate forms. The article, based on scholarly sources, reveals the interrelationship between classical genres of Eastern literature such as «nama», «dastan» and «hikayat», as well as their influence on the written literature of Turkic peoples. In particular, the influence of genre synthesis and artistic traditions in works like «Baburnama», «Shahnameh», «Muhabbatnama» and «Qabusnama» on the formation of later genres such as the novel, novel-essay, and other intermediate genres is analyzed.